A REVIEW OF STARCH DAMAGE ON PHYSICOCHEMICAL PROPERTIES OF FLOUR - Nia Ariani Putri; Ila Maratush Shalihah; Alina Femi Widyasna; Riska Putri Damayanti (University of Sultan Ageng Tirtayasa, 2020)
Starch damage is starch which is damaged by mechanical treatment, such as milling process in flour production. The purpose of this review is to determine the importance of the amount of starch damage affected by the milling process in the physicochemical properties of flour. Starch damage in flour product is influenced by some factors, such as the milling time, methods, and the roller on the milling machine. Beside milling process, the starch modification is also cause damaged to starch, such as fermentation. The presence of starch damage is an important parameter to determine the physicochemical properties of flour. Starch damage in flour will affect the physicochemical properties, such as particle size, amylose content, thermal and pasting properties, retrogradation, microstructure of starch granule, etc. It is very important to pay attention to produce the food product that have a good physicochemical characteristics. The starch damage in flour has an important role in food processing technology, for example: bread, cake, and cookies product. Furthermore, starch damage also affects the shelf life of product that has correlation with retrogradation process.